Pendampingan Murid SMA Sa’idiyah di Pesantren Salafiyah Sa'idiyah Kecamatan Arosbaya Kabupaten Bangkalan dalam Pemberian Motivasi Studi Lanjut ke Perguruan Tinggi - Amaliyah Amaliyah; Shinta Laura Federova; Muhammad Alif Fahrizal; Sherita Adventy Mustika; Muhammad Reyhan Al Aziz; Vira Tazkiyah Firdaus; Dewi Rammadhani Herlambang; Maulidya Sales; Nanda Nurul Azizah; Ismyrza Ratna Salsabila; Syafrida Purbianita (Sasambo: Jurnal Abdimas (Journal of Community Service), 2023)
Salafiyah Sa'idiyah Islamic Boarding School is one of the Islamic religious education institutions in Indonesia which is located in Arosbaya District, Bangkalan, East Java. The presence of Islamic boarding schools provides adequate religious lessons for students to face the future in a society that always experiences dynamic situations. However, the interest of students to continue their education to a higher level is still low. This is due to several factors such as economic, environmental factors and a lack of understanding of the importance of college. Another obstacle is regarding the thought of early marriage. the students of Sa'idiyah High School who tend to have the perspective of getting married rather than continuing their education. This is because the culture of thinking about marriage to avoid adultery has been firmly entrenched in Sa'idiyah High School students, so that the interest of students at Sa'idiyah High School is relatively low in continuing their education from school level to university. The method used in providing assistance this was to socialize the importance of studying in college for students, asking questions and simple games. The result of this assistance was that it was found that most of the 150 students of SMA Sa'idiyah had an interest and were motivated to continue their education to tertiary level. Meanwhile, prior to the mentoring of SMA Sa'idiyah students and students, they had no interest in continuing their education at tertiary institutions. This socialization was carried out with the hope that students would have the motivation to continue their further education after graduating from high school (SMA).